Captain America : home of the brave - Waid, Mark, 1962- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2018)
Captain America takes a journey across the United States to restore his tarnished reputation, but encounters the all-new Swordsman along the way.